Versatile Preparation of Silica Nanocapsules for Biomedical Applications. (17th March 2020) - Jiang, Shuai; Mottola, Milagro; Han, Shen; Thiramanas, Raweewan; Graf, Robert; Lieberwirth, Ingo; Mailänder, Volker; Crespy, Daniel; Landfester, Katharina
Abstract: Core–shell nanocapsules are receiving increasing interest for drug delivery applications. Silica nanocapsules have been the focus of intensive studies due to their biocompatibility, versatile silica chemistry, and tunable porosity. However, a versatile one‐step preparation of silica nanocapsules with well‐defined core–shell structure, tunable size, flexible interior loading, and tailored shell composition, permeability, and surface functionalization for site‐specific drug release and therapeutic tracking remains a challenge. Herein, an interfacially confined sol–gel process in miniemulsion for the one‐step versatile preparation of functional silica nanocapsules is developed. Uniform nanocapsules with diameters from 60 to 400 nm are obtained and a large variety of hydrophobic liquids are encapsulated in the core. When solvents with low boiling point are loaded, subsequent solvent evaporation converts the initially hydrophobic cavity into an aqueous environment. Stimuli‐responsive permeability of nanocapsules is programmed by introducing disulfide or tetrasulfide bonds in the shell. Selective and sustained release of dexamethasone in response to glutathione tripeptide for over 10 d is achieved. Fluorescence labeling of the silica shell and magnetic loading in the internal cavity enable therapeutic tracking of nanocapsules by fluorescence and electron microscopies. Thus, silica nanocapsules represent a promising theranostic nanoplatform for targeted drug delivery applications. Abstract : A versatile synthetic approach is developed for the preparation of silica nanocapsules with defined core–shell structure, tunable size, flexible interior loading, and tailored shell composition, permeability, and surface functionalization that enable site‐specific drug release and therapeutic tracking for biomedical applications.